Analisis Tingkat Kemampuan Membaca Peta Pada Mahasiswa Pendidikan Geografi - Fathoniyy Sahlul Khuluqi; Putri Tipa Anasi; Hadi Wiyono; Diah Trismi Harjanti (Jurnal Penelitian Pendidikan Geografi, 2025)
The importance of map reading ability for geography education students is as a form of graduates who master map skills, both to be used in the context of teaching or other purposes. This study aims to determine how much the ability of students in reading maps, which is divided into three classifications, namely: 1) reading maps; 2) analyzing maps; and 3) interpreting maps. The sample of this research is all geography education student’s class 2022 Faculty of Teacher Training and Education Tanjungpura University which amounted to 26 people. Ability testing is done by using a test containing map reading skills outlined in the form of essay questions covering 10 tests with three classifications of ability. The data analysis technique used is the presentative formula to see how much the value of map reading skills in students. The results of this study showed that 1) the ability to read maps scored 73.07%; 2) the ability to analyze maps scored 77.40%; and 3) the ability to interpret maps scored 42.94%. Based on the total ability, the average score of students' ability is 64.90% with the classification of good ability.